GOCEKAN AS A POWER RELATIONS IN BATUAN VILLAGE, GIANYAR, BALI - Dewi Wahyuni, Ni Made; Suka, Industri Ginting; Kebayantini, Ni Luh Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
Gocekan is a series of percussion rituals with brawls that are carried out routinely every year starting on the kajeng kliwon enyitan sasih kalima (mid-November) to Ngembak Geni, the end of the sasih kesanga (mid-March) in the Puseh Temple area in Batuan Village, Gianyar, Bali. In its development shocks have been influenced by various interests due to the power relations that occur in the implementation process. This study aims to address the main problems, namely regarding the forms of power relations, the driving factors for power relations, and the meaning and impact of power relations in shocks. Based on research there are several forms of power relations in shocks, namely the relations of hegemonic ideological power, symbolic power relations, and the power relations of domination practice. The factors that encourage power relations in shocks can be divided into two, namely internal factors consisting of beliefs (religious), cultural sacralization, openness of traditional villages, and lack of understanding of religious and legal norms. External factors consisting of capitalism, tourism and the economy. In this regard, the meaning due to the power relations in shocks is the symbolism of religious ritual and impunity. As a result it will have an impact on the deviation of the implementation of Hinduism, deviations of morality and power, and metajen habits as a subculture of the Balinese. Keywords: shock, clubbing, power relations, interests